2019
DOI: 10.17535/crorr.2019.0026
|View full text |Cite
|
Sign up to set email alerts
|

Optimality conditions for a bilevel optimization problem in terms of KKT multipliers and convexificators

Abstract: In this paper we investigate a bilevel optimization problem by using the optimistic approach. Under a non smooth generalized Guignard constraint qualification, due the optimal value reformulation, the necessary optimality conditions in terms of convexificators and Karush-Kuhn-Tucker (KKT) multipliers are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Decomposition cuts were developed in order to extend the concept of concavity cuts for deeper cuts [8,11,12]. Some other relevant research can also be found; see for example [2,4,5,14].…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition cuts were developed in order to extend the concept of concavity cuts for deeper cuts [8,11,12]. Some other relevant research can also be found; see for example [2,4,5,14].…”
Section: Introductionmentioning
confidence: 99%